Preserving Tradition and Celebrating the Prophet: An Ethnographic Study of the Mbelu’ Pandang Tradition West Sumbawa, Indonesia - Sarah, Fidlia Mae; Ilmiawan, Ilmiawan; Afandi, Ahmad; Ali, Ibrahim; Sidik, Mohamad Dindin Hamam (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2023)
This ethnographic study delves into the Mbelu’ Pandang tradition, a unique cultural practice held in Labuan Kertasari Village, West Sumbawa, Indonesia. This tradition, which originated from the Selayar tribe, involves intricate rituals such as the rolling of pandan leaves and the slicing of pandanus, performed during the commemoration of the Prophet Muhammad’s birthday. The study aimed to explore the historical roots, philosophical meanings, and contemporary significance of the Mbelu’ Pandang tradition, emphasizing its socio-cultural and religious values. Data was collected over three months using participant observation, in-depth interviews with 13 key informants, including village elders, religious, and community leaders, and qualitative content analysis was employed to interpret the findings. Results indicate that the tradition serves multiple functions: fostering community cohesion, acting as a conduit for religious expression, and reinforcing cultural identity among the villagers. It also highlights the efforts to preserve this tradition through local festivals and community-based initiatives, which sustain cultural heritage and promote regional tourism. The study contributes to understanding the dynamics of cultural preservation within minority tribes and offers insights into the complex interplay between tradition, religion, and modernity in rural Indonesia.